Bihar Second Five-Year Plan Progress Report for the Period Ending December, 1959 - Planning Commission (Planning Commission, 1959)
The latest figures of expenditure under principal Heads of Development and groups of development schemes received from the departments differ from their earlier counter parts in respect of all the three years, 1956 to 1959, for which actuals are available. In the absence of scheme wise details of these revised figures, which are still awaited from departments, the following corrected and actuals of expenditure are given in place of the statement at page I of this publication.
Bihar